2022
DOI: 10.1002/ptr.7439
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract ameliorates atherosclerosis via rebalancing gut flora and microbial metabolism

Abstract: The Ginkgo biloba leave extract (GbE) is widely applied in the prevention and treatment of atherosclerotic cardiovascular diseases in clinical practice. However, its mechanism of actions has not been totally elucidated. In this study, we confirmed the beneficial effects of GbE in alleviating hypercholesterolemia, inflammation and atherosclerosis in Ldlr À/À mice, which were fed 12 weeks of Western diet (WD). Moreover, 16S rRNA sequencing revealed that GbE treatment reshaped the WDperturbed intestinal microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Currently, targeting of the intestinal microbiota has been proposed as a prospective therapeutic strategy to ameliorate the pathology of AD [ 31 ]. Ginkgo biloba extract (EGb) has been shown to alleviate neurodegenerative diseases, depression [ 32 ], and atherosclerosis [ 33 ] and restore intestinal integrity through the brain–gut axis [ 34 ]. However, its precise mechanism of action has not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, targeting of the intestinal microbiota has been proposed as a prospective therapeutic strategy to ameliorate the pathology of AD [ 31 ]. Ginkgo biloba extract (EGb) has been shown to alleviate neurodegenerative diseases, depression [ 32 ], and atherosclerosis [ 33 ] and restore intestinal integrity through the brain–gut axis [ 34 ]. However, its precise mechanism of action has not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The extract of Ginkgo Folium is an extensively used medicine and dietary supplement in clinical to prevent and treat cardiovascular disease. In Ldlr − / − mice, one atherosclerosis animal model, Wang et al found Ginkgo Folium leads to the decreasing of the Firmicutes/Bacteroidetes ratio and the elevating of Akkermansia , Alistipes , Alloprevotella , and Parabacteroides , further promotes the generation of gut microbial metabolites, such as short chain fatty acids (SCFAs), indole-3-acetate and secondary bile acids (BAs), which dramatically associate with the atherosclerotic plaque areas ( Wang et al, 2022 ). Ginkgolide B, an active component of Ginkgo Folium , could also decrease the levels of trimethylamine (TMA) and trimetlylamine oxide (TMAO) in a gut microbiota-depended manner, which is mainly embodied by the enhancement of Bacteroides and the decline of Helicobacter and Roseburia ( Lv et al, 2021 ).…”
Section: Gut Microbiota Is a Bridge Linking Pharmacological Effect Of...mentioning
confidence: 99%
“…In these studies, inhibition of the activity of selected bacterial taxa was demonstrated, and the results became the basis for further research on anti-bacterial activity. In recent years, ginkgetin [ 129 , 133 ], amentofavone [ 132 ], ginkgolic acid C15:1 monomer [ 134 ] and polyprenol [ 135 ] and the effectiveness of leaf extracts obtained with the use of various solvents (water, ethanol, chloroform and methanol) [ 136 , 137 , 138 , 139 ]. The group of microorganisms has been significantly expanded, including taxa of gram-positive and gram-negative bacteria [ 125 , 126 , 134 , 136 , 138 , 140 , 141 ], intestinal microflora typical of the tested mammalian organisms [ 137 , 139 ], as well as human pathogenic fungi (e.g., Candida albicans used in the study by) [ 141 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In recent years, ginkgetin [ 129 , 133 ], amentofavone [ 132 ], ginkgolic acid C15:1 monomer [ 134 ] and polyprenol [ 135 ] and the effectiveness of leaf extracts obtained with the use of various solvents (water, ethanol, chloroform and methanol) [ 136 , 137 , 138 , 139 ]. The group of microorganisms has been significantly expanded, including taxa of gram-positive and gram-negative bacteria [ 125 , 126 , 134 , 136 , 138 , 140 , 141 ], intestinal microflora typical of the tested mammalian organisms [ 137 , 139 ], as well as human pathogenic fungi (e.g., Candida albicans used in the study by) [ 141 ]. In all the studies carried out, different effects on the activity of microorganisms were shown, and the strength of the effect depends on the tested pathogen and the dose/amount of the substance used.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation